2008
DOI: 10.1093/jn/138.6.1172
|View full text |Cite
|
Sign up to set email alerts
|

Proteins Activate Satiety-Related Neuronal Pathways in the Brainstem and Hypothalamus of Rats3

Abstract: Our objective was to study the relationship between the satiety induced by high-protein meals and the activation of brain areas involved in the onset of satiety. In rats, we used immunohistochemistry to monitor brain centers activated by a meal by receiving information from the gastrointestinal tract or via humoral pathways. In the nucleus of the solitary tract (NTS), the acute or chronic intake of high-protein meals led to increased activation of the noradrenergic/adrenergic neurons involved in cholecystokini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 56 publications
0
40
0
2
Order By: Relevance
“…Additionally, because dietary protein is believed to be an important factor for inducing satiety in humans and rats, the consumption of a protein-restricted diet could have lead to a decreased degree of satiety and consequently to an increased appetite. 29,30 We conclude that soy protein isolate as the protein source in a low-protein diet (40 g/1,000 kcal ME/kg) is beneficial for the management of dogs with CPSS. Such a diet should be the 1st choice in long-term support of these patients as an alternative for surgery, but also for preparation for surgery.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, because dietary protein is believed to be an important factor for inducing satiety in humans and rats, the consumption of a protein-restricted diet could have lead to a decreased degree of satiety and consequently to an increased appetite. 29,30 We conclude that soy protein isolate as the protein source in a low-protein diet (40 g/1,000 kcal ME/kg) is beneficial for the management of dogs with CPSS. Such a diet should be the 1st choice in long-term support of these patients as an alternative for surgery, but also for preparation for surgery.…”
Section: Discussionmentioning
confidence: 87%
“…The activation of POMC neurons is also inseparable from the behaviour of another population in the ARC, neuropeptide Y (NPY)/Agouti-related peptide (AgRP) neurons, activation of which is potent in increasing food intake and inhibiting POMC neuron activation (98) . We have shown that after the ingestion of a HP meal, the numbers of double-labelled Fos and a-melanocytestimulating hormone (a marker of POMC neuron activation) marked cells increased, concomitantly with a reduction in the activation of non-POMC neurons (97) . This result was less pronounced when a HP diet had been served chronically (21 d) than in an acute setting.…”
Section: Protein-induced Reduction In Eating and Central Neuronal Patmentioning
confidence: 90%
“…Faipoux et al (97) showed that a reduction in food intake after a HP load (v. a NP load) resulted from activation of the noradrenergic neurons related to CCK-induced anorexia. This study also showed that neurons expressing GLP-1 were not activated, which is consistent with the fact that protein-induced reduction in eating is not associated with conditioned food aversion (36) .…”
Section: Protein-induced Reduction In Eating and Central Neuronal Patmentioning
confidence: 99%
“…Convergent functional and anatomical evidence in rats established that the high-protein diet effect is due to an increased satiety signaling rather than a low palatability of the diet or the induction of the conditioned taste aversion (20). Although an earlier study points to an initial orosensory preabsorptive poor palatability (37), subsequent results obtained using two choices and flavor testing, behavioral satiety sequence, taste reactivity in response to different percentages or sources of proteins support that the determinant of reduced daily energy intake in rats eating a high-protein diet is a protein-specific food intake-suppressive mechanism (4,5,19,30,31). Of relevance are also choice study experiments showing that rats select a casein-containing diet (40% protein) over other proteins (46), further supporting the enhanced acceptability of casein used in the present study (50% protein from casein, 52% protein in total).…”
Section: Table 2 Fold-changes In Intestinal Hormones After 2-h Dark-mentioning
confidence: 99%
“…In view of the paucity of studies on the levels of postprandial circulating gut hormones in response to a high-protein diet in nonobese or diet-induced obese rats, additional investigations on their variations and contributions under these conditions will provide more insight into the role of hormonal mechanisms in the high-protein diet-induced curtailing of food intake. Recent evidence that the melanocortin pathway in the arcuate nucleus, a hypothalamic region with weaker blood-brain barrier and, therefore, sensitive to circulating nutrients and/or hormones (39), is activated by a 50% protein diet (19), supports such as possibility. Future studies will be needed to elucidate the full extent to which alterations in circulating gut hormones and signaling pathways within the arcuate nucleus contribute to the suppression of feeding in diet-induced obese rats fed a highprotein diet.…”
Section: Perspectives and Significancementioning
confidence: 99%